Analysis of Health Profile and Lifestyle Risk of Cardioneurology Diseases of Nursing Students at Poltekkes Kemenkes Kendari - Reni Devianti; Dwi Purnama Putri P; Dian Yuniar Syanti (Poltekkes Kemenkes Kendari, 2026)
Cardioneurology diseases currently show an increasing incidence, contributing to a high number of deaths, disabilities, and a significant economic burden due to the disease. This condition occurs globally, including in Indonesia. In 2022, the Ministry of Health released data showing heart disease and stroke as the highest causes of death in Indonesia. One-third of the deaths from heart disease and stroke occur at a young age. Objective: to identify the risk factors for cardioneurology diseases based on the health profile and lifestyle of students. Method: this research is a descriptive study involving 100 respondents with a stratified random sampling technique. Results: based on the health profile, the biggest risk factor among students is stress levels, with 82% experiencing moderate stress, 50% exposed to cigarette smoke, and 46% having a family history of cardioneurology diseases. In terms of lifestyle, the biggest risk factor is an unhealthy diet, with 85% consuming fast food more than 3 times a week, 81% lacking vegetable and fruit consumption, 71% lacking physical activity, and 46% having poor sleep patterns. The majority of respondents have 3 or more risk factors, accounting for 73%. Conclusion: the health profile and lifestyle of students contribute as risk factors for cardioneurology diseases. Suggestion: aggressive efforts are needed in promotive and preventive interventions in the prevention and control of cardioneurology diseases in adolescen